Türkçe (Turkey Health Literacy Journal, 2025)
Migration refers to the relocation of individuals for better living conditions, due to the lack of security or economic reasons. It has shaped social, cultural, and economic structures throughout history, influencing both individual lives and societies. Particularly after the onset of the Syrian civil war in 2011, the concept of “forced migration” has gained prominence in Türkiye. Forced migration involves individuals compelled to leave their regions due to wars, natural disasters, or human rights violations. Asylum seekers and refugees often face multidimensional challenges, including language barriers, cultural differences, and social exclusion. Migration health encompasses a holistic approach aimed at preserving the physical, mental, and social well-being of the person. Hosting the largest asylum seeker and refugee population globally, Türkiye has become a key player in international migration health. Civil Society Organizations (CSO) play critical roles in promoting health literacy, cultural adaptation, and strengthening primary healthcare services. Strengthening public-CSO partnerships, leveraging digital solutions to facilitate service accessibility, and ensuring long-term financial support are vital for sustainable solutions in migration health. With its comprehensive approach, Türkiye not only supports the health and integration of asylum seekers and refugees but also serves as a model for best practices on a global scale, contributing to societal health and cohesion.